An Investigation on a Crystalline-Silicon Solar Cell with Black Silicon Layer at the Rear - Zhou, Zhi-Quan (Nanoscale Res Lett, 2017)
Crystalline-Si (c-Si) solar cell with black Si (b-Si) layer at the rear was studied in order to develop c-Si solar cell with sub-band gap photovoltaic response. The b-Si was made by chemical etching. The c-Si solar cell with b-Si at the rear was found to perform far better than that of similar structure but with no b-Si at the rear, with the efficiency being increased relatively by 27.7%. This finding was interesting as b-Si had a large specific surface area, which could cause high surface recombination and degradation of solar cell performance. A graded band gap was found to form at the rear of the c-Si solar cell with b-Si layer at the rear. This graded band gap tended to expel free electrons away from the rear, thus reducing the probability of electron-hole recombination at b-Si and improving the performance of c-Si solar cell.